حق المرأة في الميراث، دراسة نقدية لاتفاقية سيداو في ضوء القرآن الكريم - طلبة الدراسات العليا بجامعة قطر نموذجاً-: Women’s Right to Inheritance, A Critical Study of CEDAW in Light of the Holy Quran: Post-Graduate Students at Qatar University as a Model - Al-Zahraa, Fatimah; Yakub@Zulkifli Mohd Yusoff,; Ali Ali Gobaili Saged, (Journal Al-Muqaddimah, 2023)
The study aims to analyze and criticize the provisions of CEDAW, which call for full equality between men and women in inheritance, and that Islam oppresses women and discriminates men from them in it. Theoretically, the study tackled a number of issues including the definition of inheritance and the clarification of the inheritance of women before Islam. The study highlighted the cases of inheritance of women in Islam, whether the cases in which women inherit half of what men inherit, or the cases in which women’s inheritance is equal to men’s, or those in which women inherit more than men, or the cases where women did not allow men to inherit at all. The study also explains the wisdom of giving men the double of women’s share in some cases, presenting the rational evidences to respond to the claim of inequality in Islam between men and women in inheritance and comparing the system of inheritance in Islam with the ancient and modern laws on the inheritance of women. The study concluded with a field study which aimed at measuring the awareness and monitoring the views concerning the equality between men and women in inheritance as approved by CEDAW, the extent of their agreement with Islamic Law and their suitability of their application in contemporary Islamic reality. To achieve these objectives, the study used the questionnaire as a comprehensive survey tool distributed to graduate and post-graduate students (Masters and PhD) at Qatar University for the academic year 2017-2018. The study used the historical, descriptive, analytical, critical and social survey approach. The study reached a number of results the most important of which is that the system of inheritance in Islam is not based on the undervalue of the women’s rights or the preference of men to women, but rather it is based on rules and principles which intend to achieve full justice between them. Furthermore, the cases where the male inherits as much as two females inherit are not all the cases of inheritance, but there are many cases where the inheritance of females and males is the same. Nevertheless, there are even cases where females inherit more than males; sometimes females inherit the double of what males inherit, and importantly in some cases females inherit while the male do not.